PENGARUH TEKANAN ANGGARAN WAKTU, FRAMING DAN KOMPETENSI AUDITOR TERHADAP AUDIT JUDGMENT - Ketut Tanti Kustina; Kadek Apri Suadnyani (Pusat Riset dan Publikasi, 2023)
Audit Judgment is a personal consideration or perspective of the auditor in responding to information that affects the documentation of the evidence and the decision making of the auditor's opinion on the entity's financial statements. The purpose of this study is to (1) determine the effect of framing, (2) time budget pressure, and (3) auditor competence on the auditor's judgment judgment. This research was conducted at the Indonesian Republic of Indonesia's Supreme Audit Board. The number of samples used was 36 respondents through the Non Probability sampling method with saturated sample technique. The type of data in this study uses quantitative data with data collection techniques in the form of questionnaires that are measured using a Likert scale and instrument testing namely the validity test and the reliability test, with the classic assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, the model feasibility test (coefficient of determination, F Test Statistic) and Hypothesis Test (t Test) using SPSS version 15. The results of this study indicate that: 1) Framing has a significant positive effect on audit judgment, 2) Time budget pressure has a significant negative effect on audit judgment, 3) auditor competence has a significant positive effect on audit judgment, as well as together time budget pressure, framing, and auditor competence have a significant effect on audit judgment. the degree of influence of the independent variables on the dependent variable is 90.8%, while the remaining 9.2% is influenced by other variables outside of this study.